SINTESIS FURFURAL DARI KULIT BUAH KAPUK RANDU DENGAN KATALISATOR ASAM KHLORIDA - Ganjar Andaka (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
Hydrolysis of kapok shell in the presence of hydrochloric acid catalyst to produce furfural was studied. This objective of this work was to study the effects of catalyst concentration and reaction time on yield of furfural. The experiment were conducted by reacting kapok shell with hydrochloric acid in a three neck flask sized 500 mL equipped with stirrer, heater, condenser, and thermometer. The reaction condition studied were catalyst concentration ranging from 0,025 N to 0,2 N and reaction time from 30 minutes to 180 minutes. The concentration of furfural was analyzed to calculate the yield of furfural. The initial analysis of kapok shell obtained that the water content of 6.75%, ash content of 2.31%, and pentosan content of 22.72%. The results show that yield of furfural reached a maximum at the catalyst concentration is 8.01% and the yield of furfural reached an optimum at the reaction time for 180 minutes is 8.03%.